Islam in Africa, Islam in Globalization (American Journal of Islam and Society, 2016)
On October 15, 2105, the International Institute of Islamic Thought commemoratedAli Mazrui’s (1933- 2014) first death anniversary by convening a seminarto honor their mutual close and lasting relationship. Mazrui served as theeditor-in-chief of the American Journal of Islamic Social Sciences (2009-14),participated in many of the institute’s events, and was awarded the IIIT DistinguishedScholar Award in 2011. In addition, he bequeathed his collectionof papers and publications to IIIT.His widow Pauline Utimazrui opened the seminar by recalling how herlate husband always spoke the truth regardless of the consequences, how hedecided to attend Columbia University because so many African students weregoing there, and how he sought to bring up controversial issues to force peopleto think outside the box. She said that he was a very happy and grateful manwho appreciated others, liked to live a simple life and be in the moment, anddid not believe in accumulating wealth.Keynote speaker Ebrahim Rasool, former ambassador of South Africa tothe United States and a long-time activist who was jailed for his anti-apartheidactivities, spoke on “Ali Mazrui: Beacon at the Intersection of Islam andAfrica.” He described Mazrui as follows:Standing for justice is the point of the triangle which is least populated, orif it is populated it may well be populated in the absence of understandingthe implications of belief in the unity of God or the understanding of the dynamismof knowledge. Professor Ali Mazrui will be remembered for epitomizingthe completeness and perfection of this golden triangle [of belief,knowledge and justice], for indeed his knowledge was founded in his unflinchingcommitment to Tauhid or unity and this, in turn, impelled him towardsutilizing his intellect both towards identifying the sources of injusticein the world and positing theoretical and practical solutions towards justice.He reminded his audience how Mazrui never shied away from controversy,as can be seen in his battle with National Public Radio (NPR) in termsof his production and defense of “The Africans: The Triple Heritage,” disagreementswith much of post-colonial Africa’s ideological or philosophicalthinking, and assertion of a distinction between theological Islam and historicalIslam. On a more personal level, in 1969 he rejected an invitation extended ...